Panbiogeographic analysis of Vexillata (Nematoda: Ornithostrongylidae) and its hosts (Mammalia: Rodentia) - Escalante, Tania; Martínez-Salazar, Elizabeth A.; Falcón-Ordaz, Jorge; Linaje, Miguel; Guerrero, Ricardo (Instituto de Ecología, A.C., 2011)
A panbiogeographic analysis was carried out, based on a parsimony analysis of endemicity (PAE) to analyze the species of helminth intestinal parasites of the genus Vexillata (Nematoda: Ornithostrongylidae) and their host species, mammals of the families Geomyidae and Heteromyidae. Two analyses were undertaken, the first using only those species of Vexillata with more than two localities, and the second analyzing all localities of this genus as a single track. Three generalized tracks were obtained by the first PAE: northern coast of Venezuela, Central America and Nearctic. Only one track was identified by a parasite and its host (V. tejerai and Heteromys anomalus). It proposes the existence of two biogeographical nodes, the first is located between the northern coast of Venezuela and Central America, on the boundaries of northeast Colombia and Panama (Colombia node); and the other in Central Mexico. Those track and nodes overlap with some proposed by other authors. In general, it appears that these systems can be explained as three biotic components. In the case of the South American component might correspond with the isolation of species (V. scorzai), as well as by species that had expanded their geographical distribution (V. tejerai), it could be related to mobilism stages of their host (Heteromys).